2021
DOI: 10.1094/pdis-10-20-2270-re
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Mapping for Common Scab Resistance in a Tetraploid Potato Full-Sib Population

Abstract: Despite the negative impact of common scab (Streptomyces spp.) on the potato industry, little is known about the genetic architecture of resistance to this bacterial disease in the crop. We evaluated a mapping population (~150 full-sibs) derived from a cross between two tetraploid potatoes (‘Atlantic’ × B1829-5) in three environments (MN11, PA11, ME12) under natural common scab pressure. Three measures to common scab reaction, namely percentage of scabby tubers, and disease area and lesion indices, were found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Common scab, caused by Streptomyces species such as Streptomyces scabies , S. acidiscabies and S. turgidiscabies (Lambert and Loria 1989 ; Miyajima et al 1998 ), is an unsightly blemish disease of potatoes occurring worldwide. Previous genetic mapping studies have identified common scab QTLs on several chromosomes viz., 1, 2, 3, 4, 6, 9, 11 and 12 (Bradshaw et al 2008 ; Braun et al 2017 ; Enciso-Rodriguez et al 2018 ; Kaiser et al 2020 ; Koizumi et al 2021 ; Pereira et al 2021a ; Yuan et al 2020 ) using diploid and tetraploid populations and deploying a range of marker types. GWAS here identified QTL-MTAs on chromosomes 1, 8, 11 and 12 (Table 5 ; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Common scab, caused by Streptomyces species such as Streptomyces scabies , S. acidiscabies and S. turgidiscabies (Lambert and Loria 1989 ; Miyajima et al 1998 ), is an unsightly blemish disease of potatoes occurring worldwide. Previous genetic mapping studies have identified common scab QTLs on several chromosomes viz., 1, 2, 3, 4, 6, 9, 11 and 12 (Bradshaw et al 2008 ; Braun et al 2017 ; Enciso-Rodriguez et al 2018 ; Kaiser et al 2020 ; Koizumi et al 2021 ; Pereira et al 2021a ; Yuan et al 2020 ) using diploid and tetraploid populations and deploying a range of marker types. GWAS here identified QTL-MTAs on chromosomes 1, 8, 11 and 12 (Table 5 ; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The software described in this study and used in this analysis has been previously used to create linkage maps and map QTL for various traits in other polyploid crops. The MAPpoly and QTLpoly software have been successfully used to map common scab resistance in autotetraploid potatoes ( da Silva Pereira et al, 2021 ) and fruit firmness in autotetraploid blueberry ( Cappai et al, 2020 ). This software has been used extensively to study autohexaploid sweet potatoes for root-knot nematode resistance ( Oloka et al, 2021 ), carotenoid, and starch biosynthesis ( Gemenet et al, 2020 ) and yield component traits ( da Silva Pereira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic interactions regulate PVY resistance and have an impact on tuber quality and quantity [6]. Furthermore, potato surveys benefit from the availability of the potato genome and sequencing progress with increasing precision genomic information, pan-genomics [7,8], advanced segregant populations [9,10], and genome editing techniques [11,12]. Tilling, ecotilling, and virus-induced gene silencing techniques have been used to link traits to genetic variants in potato [13].…”
Section: Introductionmentioning
confidence: 99%